VESPA LOVERS COMMUNITY PEKANBARU (Studies Community Activities As Capital) - Lubis, Multri Karmila; Hidir, Achmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study, entitled Community Vespa lovers Pekanbaru study of community activity as capital. Researchers raised this theme because in Pekanbaru. has a lot of historic heritage from ancient times, one of which is vespa who coined special attraction, despite being a rare commodity, but still exist. This is the background formed vespa communities in Pekanbaru City One of them is the Community vespa Uvorable comprising young people, namely students.The theory used in this study dalah Boerdieu theory of habitus, Arena and Capital. This research is qualitative descriptive. The samples in this study using purposive sampling technique (purposive sampling). Pengambian sample is intended to illustrate the focal point of this research through mutual support information. The focus of this study lies in the profile and activity Uvorable Vespa community. The collection of data through observation, interviews and documentation.From the research results obtained show that the community members Uvorable vespa vespa quite heterogeneous in meaning. Vespa has a different kind according to the ability of each member and the Vespa Uvorable diverse community activities. There is an internal activity and external activity. Capital through community activities to get a result in the form of a wide social network as they are pretty good association.Key word : Community, Vespa lovers, Activities